Technology Assessment and Forecasting of Medical Expert Systems (MEST) - Gottinger, H. W. (Methods of Information in Medicine, 1988)
This paper provides an analytical framework for technology assessment of emerging medical expert system technology (MEST). It is argued that expert system technology, though based on different principles of technological design, emanates generically from computerized systems of medical decision-making and automated decision aids.A taxonomic decision procedure is developed to assess comprehensively the benefit/cost impacts of prototypical MEST.The results obtained will be used in a technology diffusion model to forecast the spread of the use of MEST among major teaching and research hospitals. Key factors likely to constrain the use of MEST will be subject to additional evaluation.
Keywords: Technology Assessment; Technological Forecasting; Medical Expert Systems